(untitled) (Konturen, 2020)
We tend to think of migrants as moving between states and borders as fortifications of states. I would like to prove the reverse: that migrants produce and reproduce the state in the first place. I think we have got this story backward, and I think a very different politics would arise by getting this the right way round. I would like to try and rethink political philosophy starting from the figure of the migrant.